Circumsporozoite-specific T cell responses in children vaccinated with RTS,S/AS01E and protection against P falciparum clinical malaria. - Olotu, A; Moris, P; Mwacharo, J; Vekemans, J; Kimani, D; Janssens, M; Kai, O; Jongert, E; Lievens, M; Leach, A; Villafana, T; Savarese, B; et al. (2011)
BACKGROUND: RTS,S/AS01(E) is the lead candidate pre-erythrocytic malaria vaccine. In Phase IIb field trials the safety profile was acceptable and the efficacy was 53% (95%CI 31%-72%) for protecting children against clinical malaria caused by P. falciparum. We studied CS-specific T cell responses in order to identify correlates of protection. METHODS AND FINDINGS: We used intracellular cytokine staining (for IL2, IFNγ, and TNFα), ex-vivo ELISPOTs (IFNγ and IL2) and IFNγ cultured ELISPOT assays to characterize the CS-specific cellular responses in 407 children (5-17 months of age) in a phase IIb randomized controlled trial of RTS,S/AS01(E) (NCT00380393). RTS,S/ AS01(E) vaccinees had higher frequencies of CS-specific CD4+ T cells producing IFNγ, TNFα or IL2 compared to control vaccinees. In a multivariable analysis TNFα(+) CD4(+) T cells were independently associated with a reduced risk for clinical malaria among RTS,S/AS01(E) vaccinees (HR = 0.64, 95%CI 0.49-0.86, p = 0.002). There was a non-significant tendency towards reduced risk among control vaccinees (HR = 0.80, 95%CI 0.62-1.03, p = 0.084), albeit with lower CS-specific T cell frequencies and higher rates of clinical malaria. When data from both RTS,S/AS01(E) vaccinees and control vaccinees were combined (with adjusting for vaccination group), the HR was 0.74 (95%CI 0.62-0.89, p = 0.001). After a Bonferroni correction for multiple comparisons (n-18), the finding was still significant at p = 0.018. There was no significant correlation between cultured or ex vivo ELISPOT data and protection from clinical malaria. The combination of TNFα(+) CD4(+) T cells and anti-CS antibody statistically accounted for the protective effect of vaccination in a Cox regression model. CONCLUSIONS: RTS,S/AS01(E) induces CS-specific Th1 T cell responses in young children living in a malaria endemic area. The combination of anti-CS antibody concentrations titers and CS-specific TNFα(+) CD4(+) T cells could account for the level of protection conferred by RTS,S/AS01(E). The correlation between CS-specific TNFα(+) CD4(+) T cells and protection needs confirmation in other datasets.